2010
DOI: 10.1038/emboj.2010.229
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of speed and accuracy of decoding in translation

Abstract: The speed and accuracy of protein synthesis are fundamental parameters for understanding the fitness of living cells, the quality control of translation, and the evolution of ribosomes. In this study, we analyse the speed and accuracy of the decoding step under conditions reproducing the high speed of translation in vivo. We show that error frequency is close to 10 À3 , consistent with the values measured in vivo. Selectivity is predominantly due to the differences in k cat values for cognate and near-cognate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
132
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(145 citation statements)
references
References 42 publications
(128 reference statements)
10
132
1
2
Order By: Relevance
“…The Mg 2 þ concentration is crucial for speed and fidelity of decoding 16 ; however, its effect on recoding events, such as bypassing, is not known. At low Mg 2 þ concentration, the gene 60 mRNA was translated up to the stop codon at the beginning of the gap, but the full-length byp was not formed (we have added 3.5-4.0 mM Mg 2 þ , corresponding to about 1.0-1.5 mM of free Mg 2 þ , taking into account the Mg 2 þ bound to GTP and phosphoenol pyruvate present in the reaction mixture 16 ; see Methods). At higher concentrations of Mg 2 þ (5-7 mM added), the byp was formed (23%).…”
Section: Resultsmentioning
confidence: 99%
“…The Mg 2 þ concentration is crucial for speed and fidelity of decoding 16 ; however, its effect on recoding events, such as bypassing, is not known. At low Mg 2 þ concentration, the gene 60 mRNA was translated up to the stop codon at the beginning of the gap, but the full-length byp was not formed (we have added 3.5-4.0 mM Mg 2 þ , corresponding to about 1.0-1.5 mM of free Mg 2 þ , taking into account the Mg 2 þ bound to GTP and phosphoenol pyruvate present in the reaction mixture 16 ; see Methods). At higher concentrations of Mg 2 þ (5-7 mM added), the byp was formed (23%).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been argued that similar K M values for the cognate and non-cognate complexes would lead to slow cognate amino acid incorporation owing to competition by the large excess of incorrect ternary complexes over correct ones [65,66]. However, competition experiments showed that, although the presence of excess bulk ternary complexes reduced the rate of GTP hydrolysis for the cognate ternary complex about 10-fold, this is not reflected in a decrease of the rate of cognate peptide bond formation, because the rate of GTP hydrolysis even at high concentrations of inhibitory ternary complexes is higher than the rate of peptide bond formation, buffering the inhibition by competition (figure 3b) [37]. Thus, the high speed of GTP hydrolysis on cognate codons in fact causes a loss of intrinsically available selectivity, but at the same time precludes that the rate of amino acid incorporation is decreased by competition with bulk ternary complexes.…”
Section: Trade-off Between Speed and Accuracymentioning
confidence: 99%
“…Based on the available data, the reaction rate is limited by the accommodation of the aa-tRNA in the peptidyl transferase centre on the 50S subunit [37,57]. Computer simulations of accommodation suggested a stepwise movement of the tRNA through a corridor of conserved rRNA bases, which engage in various interactions with the tRNA during this movement [58].…”
Section: The Crucial Forward Steps Of Decodingmentioning
confidence: 99%
See 2 more Smart Citations